Protecting Consumers as the Buyers and Users of Cosmetic Products in the Light of European Parliament and Council Regulation (EC) No 1223/2009 on Cosmetic Products - Michałowska, Kinga (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The article focuses on the legal classification of cosmetic products and the protection of consumers as the buyers of cosmetics products. Provided under the international and the national legal systems, the protection is guaranteed by two equally valid legal bases: the Regulation of the European Parliament and of the Council (EC) of 30 November 2009, No 1223/2009 on cosmetic products and the Act of 30 March 2001 on cosmetic products. Due to the practical difficulties that attend classifying a product as a cosmetic or otherwise, the issue of determining the similarities and differences between a cosmetic product, a medicinal product and a medical device are discussed. Reference is made also to the issue of the qualifications of the persons providing cosmetic services, and who apply cosmetic products, and the liability that falls upon these individuals.